Analysis of Financial Literacy on Interest in Saving in Students of Universitas Pembangunan Panca Budi - Rizka Putri Rahmadhani; Maya Macia Sari (Journal of Research in Social Science and Humanities, 2025)
This research was conducted to find out and analyze the influence of financial literacy on saving interest. The measurement of financial literacy used in this study is financial knowledge and financial attitudes. The location of this research was carried out in the employee class of the Management Study Program, Panca Budi Development University. This type of research is a descriptive research with a quantitative approach. The research method was multiple linear regression analysis with a sample of 100 employees. The results of the study showed that partially the variable of financial knowledge did not affect the interest in saving for employees. Financial attitude variables have a significant positive effect on employees' interest in saving. Meanwhile, simultaneously, the variables of financial knowledge and financial attitudes have a significant positive influence on the dependent variables of employees' interest in saving